2006
DOI: 10.1523/jneurosci.4382-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

No Functional Magnetic Resonance Imaging Evidence for Brightness and Color Filling-In In Early Human Visual Cortex

Abstract: The brightness and color of a surface depends on its contrast with nearby surfaces. For example, a gray surface can appear very light when surrounded by a black surface or dark when surrounded by a white surface. Some theories suggest that perceived surface brightness and color is represented explicitly by neural signals in cortical visual field maps; these neural signals are not initiated by the stimulus itself but rather by the contrast signals at the borders. Here, we use functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 73 publications
13
67
0
Order By: Relevance
“…The extent of spread was comparable to that found in V1 and V2 for responses to luminance and color edges (Cornelissen et al 2006). The spread would thus not necessarily imply suppression of maskrelated activity.…”
Section: Functional Mri Experimentssupporting
confidence: 72%
“…The extent of spread was comparable to that found in V1 and V2 for responses to luminance and color edges (Cornelissen et al 2006). The spread would thus not necessarily imply suppression of maskrelated activity.…”
Section: Functional Mri Experimentssupporting
confidence: 72%
“…The most convincing evidence comes from neurophysiological recordings in the cat (Rossi and Paradiso, 1999;Rossi et al, 1996), which showed that in about 10% of area 17 neurons with their receptive fields (RFs) placed within the probing region, activity was modulated in anti-phase to inducer luminance (i.e., activity correlated to perceived brightness changes). Two human studies using functional magnetic resonance imaging (fMRI) have reported data that appear in agreement with the neurophysiological data (Pereverzeva and Murray, 2008; van de Ven et al, in preparation), whereas a third fMRI study (Cornelissen et al, 2006) did not observe a brightness induction correlate in early visual cortex.The model we propose contains three main parts (Fig. 1).…”
mentioning
confidence: 62%
“…Peters, Jans, van de Ven, De Weerd, & Goebel, 2010;Roe et al, 2005;Ramsden et al, 2001), although this effect may be smaller compared with V2, and our paradigm or stimulus may not have been sensitive enough to pick up the effect in V1. Some fMRI studies, in fact, did not find a brightness correlate in neither V1 nor extrastriate cortex using brightness induction (Cornelissen et al, 2006;Perna et al, 2005) as experimental paradigms.…”
Section: Discussionmentioning
confidence: 95%
“…Antiphase signals attenuate each other when they spread into each otherʼs retinotopic territory. Point spread of the fMRI signal has been estimated to be on the order of just a few millimeters (Engel, Glover, & Wandell, 1997;Sereno et al, 1995), but recent estimates suggested spread of approximately 7 mm at half-width-at-half-maximum (HWHM; Cornelissen et al, 2006). According to an estimate of V1 cortical magnification (Sereno et al, 1995), the distance from the inner to the outer border of the probing region projected on V1 is about 15 mm.…”
Section: Stimulus Designmentioning
confidence: 99%
See 1 more Smart Citation